Cadmium’s silent sabotage: unveiling its impact on antibiotic efficacy - Tao, Xuan; Zhou, Hong; Yu, Haoda; Wu, Yan; Bian, Tao (Frontiers in Microbiology, 2025)
Despite advancements in non-antibiotic therapies, antibiotics continue to be the cornerstone of bacterial infection management. However, the overuse of antibiotics has led to an increase in clinical failures, a situation worsened by the phenomenon of bacterial antibiotic tolerance, which remains less understood than genetic resistance. Environmental stressors, including heavy metals like cadmium, have been associated with heightened susceptibility to infections, yet their influence on antibiotic efficacy has not been thoroughly investigated. In this study, we demonstrate that chronic exposure to cadmium diminishes the effectiveness of antibiotics in systemic infections, as evidenced by a mouse model. From a mechanistic perspective, alterations in the composition of endogenous metabolites due to changes in gut microbiota, notably the diminished production of DL-mevalonolactone, impede bacterial clearance. This is because DL-mevalonolactone plays a crucial role in facilitating the eradication of antibiotic-tolerant bacteria by activating their metabolic processes. Our findings underscore the detrimental impact of cadmium on antibiotic treatment, emphasizing the health risks associated with cadmium exposure.